Pendidikan Karakter Melalui Pendekatan Militer:: Analisis Kebijakan Gubernur Jawa Barat Dalam Mengatasi Siswa Bermasalah - M Mahbubi (Prgram Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the effectiveness of the West Java Governor's policy of sending problematic students to military camps as an effort to improve discipline and character development. This policy has sparked both support and criticism due to its reliance on a harsh, physically demanding approach, while character education in Islam emphasizes compassion and wisdom. The research employs a descriptive qualitative method with a policy analysis approach. Data was collected through interviews with education experts, Islamic Religious Education (PAI) teachers, and policy observers, as well as a review of relevant documents. The findings reveal that while this policy may create short-term physical discipline, it is less effective in fostering long-term character development, especially in terms of psychological and moral aspects. Furthermore, the policy does not fully align with the principles of character education in Islam, which prioritizes nurturing through role modeling, compassion, and understanding. Based on these findings, it is recommended that the policy be re-evaluated and adjusted to incorporate a more Islam-based approach, such as motivation, spiritual development, and role-modeling